Development of Fatigue Test Bench for Gearbox Assembly of Crawler Combine Harvester - Zhu Ruiheng; Li Yaoming; Tang Zhong; Xu Lizhang; Ma Zheng (Jixie chuandong)
Crawler combine harvesters are mostly used in paddy field operation in South China. The field operation load is complex and variable, which leads to fatigue fracture and other accidents of gearboxes under the impact of variable loads and seriously affects the trouble-free working time of the whole machine. In order to solve the problem of high fault rate of gearboxes of crawler combine harvesters, the single HST hydro-mechanical differential steering gearbox developed by the team is taken as the test object, this study designs and builds the gearbox assembly fatigue test bench, and then carries out the fatigue test of differential steering gearboxes. The test results show that the test bench can well test the comprehensive working performance and durability of differential steering gearboxes, and has advantages of simple structure, convenient installation, etc. This is of great significance to study the fatigue damage rule of differential steering gearboxes, optimize and improve the mechanical structure of gearboxes and reduce the fault rate of its internal parts in the future.